Intensitas Mengakses Online Shopping Instagram Dengan Perilaku Konsumtif - Denok Wigati; Windy Chintya Dewi; Nur Fanti Indah Sari (IDEA: Jurnal Psikologi, 2022)
The purpose of this Inferential research was to test the significance of the correlation between the Intensity of Accessing online Shopping and Consumptive Behavior. The population of this study were 56 career women. The sampling technique used is Simple Random Sampling. The data collection method used the online shopping intensity and consumption behavior scales. Test the hypothesis using Rho Spearman. The results of Rho Spearman's analysis between the variables Of Intensity of Accessing Online Shopping and Consumptive Behavior produced a rho = 0.691 correlation coefficient with Sig.or p = 0.000 (p< 0.01), meaning that there is a very significant positive correlation between the intensity of accessing online shoping and consumptive behavior. This means that the increasing intensity of access to online purchases with high consumption behavior among career women. So, the hypothesis in this study is accepted.